Down-regulation of NF-κB signaling pathway promotes epithelialization of human amniotic mesenchymal stem cells - LIU Nizhou; MAO Yanhua; ZHANG Wenwen; ZHANG Yingfeng; WANG Jia (陆军军医大学学报, 2023)
Objective To explore the role of NF-κB signaling pathway in inducing the epithelialization of human amniotic mesenchymal stem cells (hAMSCs). Methods hAMSCs were extracted and divided into control group and induced group (n=3). RT-qPCR was used to detect the mRNA levels of epithelial markers (CK-7, CK-19, E-cadherin), mesenchymal marker (Vimentin), key factors of NF-κB signaling pathway (IκBα, p65) and target gene of NF-κB pathway (cyclin D1). The protein expression of CK-7, E-cadherin, Vimentin, IκBα, p65 and p-p65 were detected by immunofluorescence assay. To confirm the role of NF-κB signaling pathway in the epithelialization of hAMSCs, hAMSCs were divided into induced group, inhibitor group, Ad-GFP group (control adenovirus), Ad-IκBα group (a recombinant adenovirus overexpressing IκBα), LV-GFP group (control lentivirus) and LV-RELA-RNAi group (a lentivirus silencing p65) (n=3). The mRNA levels of CK-7, CK-19, E-cadherin, Vimentin, IκBα and p65 were detected by RT-qPCR. The protein levels of CK-7, E-cadherin, Vimentin, IκBα, p65 and p-p65 were determined by immunofluorescence assay. Results Compared with the control group, the induced group showed the increased mRNA expression of CK-7, CK-19 and E-cadherin (P < 0.01), increased protein expression of CK-7 and E-cadherin (P < 0.05), decreased mRNA expression of Vimentin (P < 0.01), decreased protein expression of Vimentin (P < 0.05), decreased mRNA expression of IκBα, p65 and cyclin D1 (P < 0.001) and protein expression of IκBα, p65 and p-p65 (P < 0.05). Compared with the induced group, the mRNA expression levels of CK-7, CK-19 and E-cadherin were increased (P < 0.01) in inhibitor group, Ad-IκBα group and LV-RELA-RNAi group, and the protein expression of CK-7 and E-cadherin were increased (P < 0.05), while the mRNA expression of Vimentin was decreased (P < 0.01) and protein expression of Vimentin was decreased (P < 0.05). Conclusion NF-κB signaling pathway is involved in the regulation of epithelialization of hAMSCs, and down-regulation of NF-κB signaling pathway could effectively promote the epithelialization of hAMSCs.